From care inside the laboratory to the world beyond it: a multispecies ethnography of TB science towards growing a decolonised science in South Africa - Shain, Chloë-Sarah (African Gender Institute, 2023)
This anthropological research began with curiosity about human relationships with microbes. Inside the contained environment of a Biosafety Level 3 laboratory at a South African university-based tuberculosis research division, the fieldwork focused on the relationships between scientists and Mycobacterium tuberculosis − the pathogenic bacterium that causes the disease tuberculosis (TB). These deadly bacteria were cared for and nurtured by women scientists. This care extended to the cells and various species with which they worked. Moreover, this care moved beyond the scope of their immediate scientific research projects and well beyond the laboratory. Care was also central to how the participants conducted their scientific research and themselves in the world. This long-term, qualitative ethnographic research weaves together many layers of care in biomedical scientific research, highlighting that scientific research is a deeply personal, caring and subjective practice. The natural and the social are not − and can never be − mutually exclusive. Boundaries between mind/body, subject/object, human/nonhuman, researcher/researched, subjectivity/objectivity and science/society are porous. Acutely aware of the socio-political moment in which this research was embedded, these findings are put into conversation with South African student calls to decolonise science that emerged alongside the #RhodesMustFall student movement. In particular, the focus is on a 2016 meeting about decolonising science at the University of Cape Town where students argued for connection between the university and the community, science and society and the world of academia and the world of Africans. Implicit was the need for science to be relevant to Africans and deeply complex African social formations and problems. The care by women scientists that was observed inside the laboratory and beyond it speaks volumes to cultivating a more caring science and caring institutions of science that connect the laboratory to the world in which it exists in meaningful, relevant and impactful ways. I demonstrate how the participants embodied a decolonised science, and that what they cared about and how they acted upon those cares could serve as important guides for decolonising science and scientific institutions. This research provides important contributions to the field of science and technology studies (STS), to anthropological research on TB and to the conversation on decolonising science in South Africa.